1999
DOI: 10.1007/s000240050222
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Fractal Evolutions and Hierarchies for Microearthquakes in Central Greece

Abstract: Statistical characteristics of seismicity represented by microearthquakes are examined for three regions in central Greece, in particular the fractal correlation dimension, D 2 , and traditional b values are examined in tandem as a function of time by using the moving window technique. The Patras region contains the complicated tectonics, extending to damaging historical earthquakes of the western Corinth Gulf and the Rio Graben, yielding D 2 values between 0.40 and 1.20 with b between 0.94 and 1.27: unusually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In the practical calculation, the fractal dimension analysis is based on a power law and is turned into a linear law after logarithmic transformation. Therefore, sufficient data points are the key for a reliable estimate of fractal dimension based on the ensuing linear regression (XU and BURTON, 1999). SMITH (1988) suggested the minimum number of points or events required for a reliable calculation of a correlation dimension as:…”
Section: Fractal Dimension Mappingmentioning
confidence: 99%
“…In the practical calculation, the fractal dimension analysis is based on a power law and is turned into a linear law after logarithmic transformation. Therefore, sufficient data points are the key for a reliable estimate of fractal dimension based on the ensuing linear regression (XU and BURTON, 1999). SMITH (1988) suggested the minimum number of points or events required for a reliable calculation of a correlation dimension as:…”
Section: Fractal Dimension Mappingmentioning
confidence: 99%
“…The regional stress field can be nicely identified as follows: 1 NE-SW tension in Ubrique; 2 WNW-ESE compression in Malaga that might be related to the arc-shaped distribution of intermediate earthquakes existing south of this city; 3 ENE-WSW tension (and other secondary NNW-SSE depicting a radial pattern) in Granada; 4 N-S compression in Alicante. Xu and Burton (1999) reported that the coexistence of two different stress fields in a same region (central Greece), interacting with variable seismicity, could explain the relatively low intensity of the stresses (high b-value). This phenomenon may have happened in zone 2 (dominated by extension) with a less stress accumulation, making it more heterogeneous than zone 1 (dominated by compression) that is subjected to local stresses of similar direction.…”
Section: Seismotectonic Zonation and Stress Fieldmentioning
confidence: 97%
“…According to Utsu (1965), when the number of events used for the estimation exceeds 50, the maximum likelihood method gives a stable estimation of the b-value. Xu and Burton (1999) proposed a minimum of 42 earthquakes for the calculation of the dimension with the Grassberger-Procaccia algorithm, and Bhattacharya and Kayal (2003) reduced this number to 20 earthquakes inside each sample. More recently, Singh et al (2008,2009) have considered a minimum of 50 earthquakes for the calculation of the b-value and the fractal dimension.…”
Section: About the Size Of The Moving Windowmentioning
confidence: 99%
“…The fractal approach has introduced a new statistical tool to quantify the scale invariant distribution of seismicity and, with that, the properties of randomness and clusterization. Time variations of the spatial fractal dimension of seismic events have been found for different areas in the world allowing a quantitative characterisation over time of scale invariant failure processes acting in seismogenic volumes/fault zones (Lomnitz-Adler 1992, De Rubeis et al 1993, Öncel et al 1996, Tosi 1998, Xu and Burton 1999, Gospodinov et al 2012). The method often preferred for calculating the fractal dimension D on timespatial earthquake sequences is the correlation integral method (Grassberger and Procaccia 1983).…”
Section: Previous Studies On Spatial Clustering Of Earthquakesmentioning
confidence: 99%
“…The method often preferred for calculating the fractal dimension D on timespatial earthquake sequences is the correlation integral method (Grassberger and Procaccia 1983). Its simplicity and reliability with respect to the box counting algorithm has been widely discussed (among others, by Henderson et al 1992, De Rubeis et al 1993, Öncel et al 1996, Tosi 1998, Xu and Burton 1999.…”
Section: Previous Studies On Spatial Clustering Of Earthquakesmentioning
confidence: 99%